Dropping the baby and other scary thoughts : breaking the cycle of unwanted thoughts in parenthood - Kleiman, Karen R.; Wenzel, Amy (New York : Routledge, 2020)
"This accessible guide addresses the nature of the intrusive and unwanted thoughts that can be common in new parenthood, and offers practical answers and advice on how to tackle these. Written by two leading clinicians in the perinatal community, in collaboration with two promising leaders in this specialized field, Dropping the Baby and Other Scary Thoughts, 2nd edition offers a compassionate approach to breaking the cycle of scary thoughts that is invaluable to new parents and clinicians alike"--
OCLC-licensed vendor bibliographic record.
Keywords: Postpartum depression; Motherhood -- Psychological aspects; Childbirth -- Psychological aspects; Mothers -- Mental health; PSYCHOLOGY / Mental Health